2007
DOI: 10.1001/archinte.167.19.2116
|View full text |Cite
|
Sign up to set email alerts
|

Blunted Heart Rate Dip During Sleep and All-Cause Mortality

Abstract: Background: Although it has been somewhat overlooked, resting heart rate is an established predictor of cardiovascular and noncardiovascular outcome. We assessed the determinants and mortality associations of heart rate measured during ambulatory blood pressure monitoring (ABPM) to evaluate its informativeness during activity and sleep. Methods: We studied a cohort of 3957 patients aged 55 ± 16 (mean ± SD) years (58% treated for hypertension) who were referred for ABPM during 1991 to 2005. Heart rate nondippin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
102
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(111 citation statements)
references
References 21 publications
8
102
0
Order By: Relevance
“…It has been recently referred to as 'a trove of hidden gems'. 32 Such 'gems' include identification of non-dipping 33,34 and nocturnal hypertension, 33,35 the morning surge, 33,36 exposing white-coat hypertension, 33,37 uncovering masked hypertension 33 and identifying the prognostic importance of ambulatory heart rate 38,39 AASI is the most recent candidate for this list. Its predictive ability has been inconsistent and its implications somewhat vague.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently referred to as 'a trove of hidden gems'. 32 Such 'gems' include identification of non-dipping 33,34 and nocturnal hypertension, 33,35 the morning surge, 33,36 exposing white-coat hypertension, 33,37 uncovering masked hypertension 33 and identifying the prognostic importance of ambulatory heart rate 38,39 AASI is the most recent candidate for this list. Its predictive ability has been inconsistent and its implications somewhat vague.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed that a"non-dipping"BP pattern is associated with an increased risk for morbidity and mortality in patients with CVD 37)- 40) . Insomnia is prevalent (50%) in patients with HF, which is associated with autonomic dysregulation, activation of the renin-angiotensin-aldosterone system (RAAS), and lower exercise capacity, while the presence of insomnia is associated with poor clinical outcome in patients with HF 41) .…”
Section: Sleep Disorders A) Insomniamentioning
confidence: 99%
“…5 Such lack of heart rate dipping adds to the importance of nocturnal monitoring in women because it may be an independent risk marker. 5 It would be interesting to learn the IDACO findings in this matter.…”
Section: To the Editormentioning
confidence: 99%